Sedimentary facies and paleoenvironment of a Pleistocene fossil site in Nakhon Ratchasima province, northeastern Thailand - J. Duangkrayom (2018)
Quaternary fauna and flora fossils were found in situ in a sand pit at the Khok Sung village of Khok Sung Subdistrict, Muang District, Nakhon Ratchasima province. Six lithostratigraphic units from unit 1 to unit 6 in ascending order were recognized in the sand pit. The sediments in the Khok Sung sand pit were deposited as two meandering channel sets. Units 1, 2, and 3 form the lower channel sequence, and units 4, 5, and 6 form the upper channel sequence. The lower channel unconformably overlies bedrock and generally flowed northward, whereas the upper channel flowed eastward. The parent rocks of the Khok Sung sediments crop out in the western margins of the Khorat Plateau. The flora fossils include fruits (Ziziphus khoksungensis (Rhamnaceae), Dipterocarpus costatus (Dipterocarpaceae), Melia azedarach, and Dracontomelon dao (Anacardiaceae)), seeds, leaves, wood, tubers (Cyperus or Bolboschoenus (Cyperaceae)), amber, and pollen. This assemblage suggests the presence of tropical mixed deciduous and dry evergreen forests. The fauna fossils include fish, gavial (Gavialis cf. bengawanicus), tortoise (Batangur cf. trivittata, Heosemys annandalii, Heosemys cf. grandis, and Malayemys sp.), soft shell turtle (Chitra sp., and cf. Amyda sp.), bovids, rhinoceros, deer, an advanced form of Stegodon, and hyena. The fauna indicate that the climate differed from today, with heavier rainfall and more extensive grassland areas during the Pleistocene. © 2013 Elsevier Ltd and INQUA.